Uptake and correlates of influenza vaccine among older adults residing in rural regions of south China: a cross-sectional study - Zhao, Peizhen; Xu, Wenqian; Wang, Jinshen; Liang, Peng; Li, Haiyi; Wang, Cheng (Frontiers in Public Health, 2024)
Seasonal influenza continues to pose a substantial public health challenge for older adults residing in rural areas worldwide. Vaccination remains the most efficacious means of preventing influenza. This study aimed to investigate the extent of influenza vaccine coverage and identify the factors influencing vaccine uptake among older adults in rural regions of south China.A cross-sectional study utilizing convenience sampling was conducted in two rural sites in Guangdong Province. Individuals needed to meet specific inclusion criteria: (1) attainment of 60 years of age or older; (2) originating from rural households; (3) demonstrating a voluntary desire to partake in the survey, either through written or verbal informed consent. Data encompassed variables such as socio-demographic information, influenza infection and vaccination history, knowledge and attitudes towards influenza vaccination, and perceived beliefs regarding the influenza vaccine.Univariate and multivariable logistic regression analyses were employed to ascertain the factors associated with influenza vaccine utilization. In the multivariable model, adjustments were made for gender, age, legal marital status, highest educational attainment, and monthly income.A total of 423 participants were ultimately included in this study, with the majority falling within the age range of 60 to 75 years (81.3%). Only one-third of the participants had received an influenza vaccine in the past year (30.0%). Notably, nearly half of the older adults exhibited hesitancy towards influenza vaccination (45.1%). The multivariable analysis revealed that rural older people with a robust understanding of influenza vaccines and a positive attitude towards them (adjusted odds ratio [aOR] = 2.60, 95% confidence interval [CI]: 1.41-4.81), along with a high level of trust in vaccination service providers (aOR = 2.58, 95% CI: 1.01-6.63), were positively associated with receiving influenza vaccination in the past year.This study reveals a low rate of influenza vaccine uptake among older adults residing in rural areas of south China. Given the limited adoption of influenza vaccination and the significant threat it poses, there is an urgent imperative to devise precise interventions aimed at enhancing the effectiveness of influenza vaccination programs.